Socio-economic status of farmers rearing Bachaur cattle in its habitat under middle Gangetic plains - CHANDRAN, P C; DEY, A; BARARI, S K; KAMAL, REENA; DAYAL, SHANKER; CHAKRABARTI, ASIT (The Indian Journal of Animal Sciences, 2014)
Bachaur cattle, the only recognized cattle breed of Bihar, was studied for its role in uplifting the farmers in their breeding tract by visiting 53 villages in 5 blocks of Sitamarhi district in Bihar. The different practices of farming systems involving Bachaur cattle, socio-economic status of farmers and economics of rearing of Bachaur cattle were studied through standard questionnaire. The regression of different independent variables on the total income was calculated. The study revealed that 29.7 % of farmers possessing Bachaur cattle were practicing agriculture apart from rearing cattle. Literacy rate of Bachaur cattle owners ranged from 21.39 to 57.14% for different types of farmers. Marginal, small, semi-medium and medium farmers earned 91.40, 89.90, 86.31 and 87.22%, respectively, of their income from draught power of Bachaur cattle. Rearing of Bachaur bullocks supported the income of marginal, small and semi-medium farmers to the tune of 50.12, 48.31 and 42.66%, respectively. Regression of independent variables on income from Bachaur bullocks indicated that expenses incurred on maintenance of health and feeding of bullocks influenced the total income of farmers to a greater extent followed by money invested in purchasing Bachaur bullocks.